Beneficial Effects of Gracillin From Rhizoma Paridis Against Gastric Carcinoma via the Potential TIPE2-Mediated Induction of Endogenous Apoptosis and Inhibition of Migration in BGC823 Cells - Liu, Wenming; Wang, Yanting; Chen, Junjie; Lin, Zhenhe; Lin, Mengjie; Lin, Xiantong; Fan, Yanyun (Frontiers in Pharmacology, 2021)
Tumor necrosis factor-α inducible protein-8 (TIPE2), initially recognized as a negative immune regulator, exerted an important roles in suppressing the progression of numerous cancers. In our previous investigation, we found that TIPE2 expression displayed a decrease or absence in gastric tumor tissue, and the overexpression of TIPE2 suppressed the growth of gastric cancer tumor and cells, demonstrated that TIPE2 could be a potential medicinal target of gastric cancer. However, it’s seldomly reported that several medicinal agents or candidates targeted TIPE2 for treating disease including gastric cancer. To identify the candidate targeting TIPE2 to fight against gastric cancer, several extractions from traditional natural medicinal plants with anti-tumor function were employed to screen the active compounds according to bioassay-guided isolation. Interestingly, gracillin, a component from the ethyl acetate extracion of Rhizoma Paridis, was identified to induce the expression of TIPE2 and inhibit the cell proliferation in gastric cancer BGC-823 cells. Furthermore, the underlying mechanism of gracillin restraining gastric cancer were evaluated by clone formation, EdU staining , flow cytometry and other assays, meanwhile the role of TIPE2 in the anti-tumor effect of gracillin were elucidated via the apply of siTIPE2 RNA. It’s determined that gracillin could fight against gastric cancer cells via inhibiting the cell proliferation participated by PI3K/AKT pathway and cell cycle arrest, suppressing the EMT pathway-regulating cell migration and inducing bcl2-associated mitochondrial apoptosis. Additionally, TIPE2 maybe contribute to the benefits of gracillin. These results of the present study laid an important theoretical value toward the medicinal development of gracillin, and was also a benefit for understanding the effect of TIPE2 as a potential tumor target.